THE UNKNOWN HERITAGE OF BAB AL-ABWAB: "SHARH ASH-SHIHAB" OF ABU AL-QASIM AL-BABI AND "TUHFAT AL-ASHAB" OF ABU BAKR AD-DARBANDI - Alibekov, Hizri Gadzievic (History, Archeology and Ethnography of the Caucasus, 2023)
The paper explores the earliest theological work in the North Caucasus, “Sharh al-Shihab”, written by a theologian of the 11th century from Bab al-Abwab, Abu al-Qasim al-Warraq al-Babi (d. between 1098-1004). This work is a commentary on the work of an Egyptian qadi and preacher Abu Abdullah al-Quda‘i (d. 1062) “Shihab al-Akhbar”, in which the author collected various aphorisms and maxims attributed to the Prophet Muhammad. During our study, we revealed numerous lists of “Sharh al-Shihab” stored in libraries and archives in various parts of the world. Some of these lists are used in our paper in order to analyze the text of the work. The study brings to light new valuable information from the life of the Muslim community in the Caucasus in the 11-12th centuries. In the course of the study, it was found that al-Warraq’s disciple, a famous Sufi and theologian from Bab al-Abwab, Abu Bakr al-Darbandi (d. in the first third of the 12th century) also composed his own commentary on the “Shihab al-Akhbar” by al-Quda‘i, taking as a basis the commentary of his teacher. The lists of this previously unknown work, which the author entitled “Tuhfat al-Ashab fi Sharh al-Shihab”, were also uncovered. Some of them became the subject of this study. Thus, the paper examines two works of the 11-12th centuries, compiled in Bab al-Abwab. The study suggests that the writing of these works is a reflection of the general processes in the socio-religious sphere that took place in the Muslim world during the specified period.